Investigating diversity in polymer-based identity cards using ATR-FTIR spectroscopy and chemometrics - McGann, Jasmine; Willans, Meg; Sauzier, Georgina; Hackett, Mark; Lewis, Simon; McGinn, John; Trubshoe, Tonya; Van Bronswijk, Wilhelm (2020)
© 2020 The Author(s). Published by Elsevier B.V.